2017
DOI: 10.1515/jpm-2016-0400
|View full text |Cite
|
Sign up to set email alerts
|

Fetal thymus size in pregnant women with diabetic diseases

Abstract: Reduced fetal thymus size seems to be associated with diabetic pregnancy. We introduce fetal thymus size as a new potential prognostic parameter for maternal diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 22 publications
0
31
3
1
Order By: Relevance
“…Therefore, the finding of an association between fetal thymus size and ma- ternal diseases like preeclampsia (associated with a decreased thymus size; [8]) or rheumatic diseases (associated with an increased thymus size; [4]) does not apply for pregnancies complicated by T1D. This result seems contrary to two recent studies reporting a decreased fetal thymus size in pregnancies affected by maternal diabetes [4,15]. However, in both studies the ultrasound investigations were performed earlier (1st trimester or at a median gestational age of 21.0 weeks, respectively) and pregnancies were complicated by diabetes in general and not particularly by autoimmune T1D.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, the finding of an association between fetal thymus size and ma- ternal diseases like preeclampsia (associated with a decreased thymus size; [8]) or rheumatic diseases (associated with an increased thymus size; [4]) does not apply for pregnancies complicated by T1D. This result seems contrary to two recent studies reporting a decreased fetal thymus size in pregnancies affected by maternal diabetes [4,15]. However, in both studies the ultrasound investigations were performed earlier (1st trimester or at a median gestational age of 21.0 weeks, respectively) and pregnancies were complicated by diabetes in general and not particularly by autoimmune T1D.…”
Section: Discussionmentioning
confidence: 90%
“…However, in both studies the ultrasound investigations were performed earlier (1st trimester or at a median gestational age of 21.0 weeks, respectively) and pregnancies were complicated by diabetes in general and not particularly by autoimmune T1D. In one of the two studies [15], the authors reported a decreased thymus size in diabetic pregnancies complicated by gestational diabetes (n = 98) or preexisting diabetes of any type (n = 63), and suggested that metabolic disturbanc-es such as maternal hyperglycemia could be a fetal stress factor, resulting in a smaller thymus size. In contrast, we analyzed the thymus size of pregnancies with autoimmune T1D only, and excluded any other preexisting diabetes form, in particular type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes is a distinct teratogen affecting pregnancy, with newborns having congenital features overlapping with 22q11.2del (Kucera, 1971;Mills, 2010;Sacks et al, 2012;Dornemann et al, 2017). In fact, about 18% of infants with a thymic aplasia who did not have deletions on chromosome 22q11.2 and required a thymic tissue transplant were born to mothers with a clinical history of gestational diabetes (Markert et al, 2007).…”
Section: The Genetic and Epigenetic Regulation Coupled To Tbx1 Functionsmentioning
confidence: 99%
“…Maternal diabetes and systemic use of retinoic acid (RA) derivatives during pregnancy can cause long-term thymic hypoplasia in newborns (18)(19)(20)(21). What's more, gestational diabetes leads to congenital malformations in the developing fetus which overlap with those noted in individuals with 22q11.2del; hypoplasia/aplasia of the thymus, cardiac outflow tract defects, and hypoparathyroidism (160)(161)(162)(163). Estimates suggest that 18% of infants who required a thymic tissue transplant due to an aplasia of this tissue, and did not have 22q11.2del, were born to mothers who had maternal diabetes (72).…”
Section: Clinical Conditions During Pregnancy Leading To a Thymic Hypoplasia/aplasiamentioning
confidence: 99%